Implementation Of The National Cash Wakaf Movement (GNWU) Investment Solutions For Sharia Financial Products: Implementation Of The National Cash Wakaf Movement (GNWU) Investment Solutions For Sharia Financial Products - abdul royzak, abdul royzak (UMBanjarmasin, 2022)
Waqf can be useful for dealing with debris in this country because in various countries where the majority of its citizens are Muslims it has been proven that waqf can successfully complete the ruins because waqf has functions for various things including sources of financing for various social services, financing for houses illness, funding for education and others. The role of waqf is very important for this country apart from in the economic world, waqf also plays a very important role in the world of education in this country. The government places great emphasis on expanding or widening capital, strengthening skills, changing cultures in terms of reducing or minimizing social weaknesses and poverty. Therefore waqf money has links with Islamic financial institutions. Waqf is utilized especially specifically for parties in lower middle positions so that these parties can also experience various facilities and provide services that are much better or even comparable to those in the upper middle position